PENGARUH KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PANDEMI COVID-19 - Yunita Fitri Nurjanah Qoirunisa; Agustinus Kismet Nugroho Jati (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Company value is an important indicator that with good firm performance will encourage investors to invest in a company by reflecting high prosperity for shareholders, company value can increase. This study aims to analyze the effect of funding decisions, dividend policies and company size on company value during the COVID-19 pandemic. The sample used was 60 companies according to the criteria with the purposive sampling method as the sampling technique. The analysis technique used is multiple linear regression. The variables used are funding decisions, dividend policies and company value. The results of the study show that simultaneously the funding decision variables, dividend policy, company size, and covid-19 have a significant effect on company value, while partially funding decision variables have no positive effect on company value, partially dividend policy variables have a positive and significant effect on company value, partially the variable company size has a negative effect on company value, and partially the covid-19 variable has no negative effect on company value. Keywords: Funding Decision, Dividend Policy, Company Size, Covid-19, Company Value.